Performance Analysis of Advanced Hybrid Speech Coding Techniques in Time domain, Spectral domain and Perceptual domain (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Speech coding is the art of creating a minimally redundant representation of the speech signal that can be efï¬ciently transmitted or stored in digital media and decoding the signal with the best possible perceptual Quality. The speech transmission in wireless networks is associated with the reduction of extra information present in signal in such a way to preserve the quality and intelligibility of speech. It is known that the lower the bit rate the lesser the quality of the reconstructed speech however there is a constant quest to achieve a better speech quality at lower bit-rates.This paper presents performance analysis for the quality of advanced hybrid speech coding techniques in Time domain, Spectral domain and perceptual domain. These analyses are implemented on three different algorithms of advanced hybrid speech coding techniques such as CELP, G729 Annex A, G723.1 to assess the quality performance for English female speaker, English male speaker and Arabic female speaker by using Mat lab simulation program. Our evaluation criterion implemented includes the following tests: Signal to Noise Ratio (SNR), Segmental Signal to Noise Ratio (SNRseg), The Log-Likelihood Ratio (LLR), The Weighted Spectral Slope (WSS), Absolute Error,Perceptual Evaluation of Speech Quality (PESQ),NONE">Rating of speechdistortion, rating of background noise and the predicted rating of overall quality.